Nature of losses and the value relevance of earnings and book values : the case of Malaysian companies / Fatmawati Jusoh - Jusoh, Fatmawati (2005)
The purpose of this study is to investigate the role of earnings and book value in explaining market valuation for firms reporting loss. In this study, it is suggested that loss are not homogenous across firms, and specifically explores the economics of two types of loss, which are (1) transitory loss and (2) recurring loss. Transitory loss is temporary and do not reflect the ongoing economic circumstances of the firm, whereas recurring loss is consecutive loss that. are due to ongoing poor operating performance. Recurring loss could lead to either an adaptation by the firm to return to profitability or abandonment of the firm. The sample comprises of loss companies, which are listed on the Main Board of Bursa Malaysia from 1994 to 2003. An equity valuation model developed by Ohlson (1995) is employed to test the hypotheses. Additionally, logit analysis is also carried out to further examine the probability of the occurrence of the two independent variables. Two hypotheses are tested; (1) For transitory loss, earnings will have a non-negative association with market value (2) For recurring loss, earnings will have a negative association with market value. The empirical evidence for this study show mixed results over the six years analysis. VIII